Implementation of Rubber Sap Bowl Cover for Improved Rubber Harvest Quality - Dasmen, Rahmat Novrianda; Darwin, Darwin; Aldeno, Malvin; Febriyanti, Dinni (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2025)
Seri Tanjung village is a village located in the Tanjung Batu District, Ogan Ilir Regency, South Sumatra. The majority of the village’s population relies on plantation activities, particularly rubber farming, with approximately 65% of the area used for rubber production. Latex is a vital commodity for the local community and serves as a major contributor to the village’s economy. However, in practice, the quality of latex often deteriorates due to rainwater contamination. Rainwater that enters the tapping bowl can hinder the natural coagulation process and reduce the overall quality of the harvested rubber. This study aims to design an automatic bowl cover system for latex tapping, based on a rain sensor, to maintain the latex quality. The research method employed includes literature study and action research through prototype development. The test results show that the automatic cover system functions effectively and responsively in protecting the latex from rain exposure. Therefore, this tool has the potential to improve both the quality and quantity of rubber production, while also contributing to the welfare of rubber farmers in the region.Desa Seri Tanjung merupakan sebuah desa di Kecamatan Tanjung Batu, Kabupaten Ogan Ilir, Sumatra Selatan. Desa ini mayoritas penduduknya menggantungkan hidup dari sektor perkebunan, khususnya perkebunan karet, dengan sekitar 65% wilayahnya digunakan untuk produksi karet. Lateks atau getah karet merupakan komoditas penting bagi masyarakat lokal dan menjadi penopang utama ekonomi desa. Namun, dalam praktiknya, kualitas lateks sering mengalami penurunan akibat kontaminasi air hujan. Air hujan yang masuk ke dalam mangkok sadap dapat menghambat proses pembekuan alami dan menurunkan mutu karet yang dihasilkan. Penelitian ini bertujuan untuk merancang sebuah sistem penutup otomatis pada mangkok sadap getah karet berbasis sensor hujan, guna menjaga kualitas getah tetap optimal. Metode yang digunakan dalam penelitian ini adalah studi literatur dan action research melalui perancangan prototipe. Hasil pengujian menunjukkan bahwa sistem penutup otomatis ini mampu bekerja secara responsif dalam melindungi getah dari air hujan. Dengan demikian, alat ini berpotensi meningkatkan kualitas dan kuantitas produksi karet, serta berkontribusi terhadap peningkatan kesejahteraan petani karet di daerah tersebut.